Mani et Roumeli : Écrire la Grèce en dehors des sentiers battus - Jan Borm (Viatica)
Greece plays a central role in Leigh Fermor’s writing. Reading Mani and Roumeli in parallel, this article focuses on the reception of Lord Byron in and the impact of Robert Byron on Leigh Fermor’s travelogues, notably in his representations of Mount Athos and Byzantine art, while placing his accounts of life in the monastic communities, in the Mani and in Northern Greece in the context of his remarks on Greek history and identity epitomized by his discussion of what he termed the Helleno-Romaic dilemma. In doing so, Leigh Fermor’s exquisite prose reveals itself to be a striking homage to Greek civilisation off the beaten track and one of the foremost contributions to what Lawrence Durrell termed the “Greek department” of British literature.